Defining marginality in the Periurban areas of Quito: A descriptive approach based on empirical and spatial data - Riccardo Porreca; Nadia Rodriguez-Pazmi\~no; Vasiliki Geropanta; Paola Bracchi (REGION, 2023)
In Latin America, marginality is a complex phenomenon involving various geographically significant factors, including the critical, physical, social, and human aspects. Bouldering areas of cities are often excluded from infrastructural interventions and social policies. In the case of Andean countries such as Ecuador, marginality affects not only rural lands but also in-transition areas between different geographical regions, as in the case of mountainous and coastal zones. These regions are characterized by a wide range of natural resources and climate conditions, and because of their diversity and relative proximity to the major cities, they offer potential for sustainable development. Nonetheless, the lack of infrastructure affects the accessibility of these periurban areas and critically limits their interaction. Drawing on these elements, the paper seeks to investigate whether periurban areas can be considered marginal and what tools can depict an encompassing image of local marginality, stressing its advantages for the local community. Following this idea, the paper focuses on the case of Lloa, a large rural parish in the Metropolitan District of Quito (DMQ), to determine which criteria can better capture its marginality, considering it as a periurban in-transition area. The paper suggests a cross-discipline methodology to push the limits of the field through the review of a significant body of literature and a thorough qualitative and quantitative analysis of the case study. Finally, the paper emphasizes the inadequacy of the current forms of planning to effectively define the marginality of periurban areas as a whole in the region by reflecting on the case study and through an analysis of the existing land use plans.
Keywords: 330; marginality; Metropolitan District of Quito; landscape; periurban